Earliness–tardiness minimization on scheduling a batch processing machine with non-identical job sizes. (September 2015) - Li, Zhongya; Chen, Huaping; Xu, Rui; Li, Xueping
Highlights: Minimize earliness–tardiness ( E / T ) on a single batch processing machine. Consider jobs with a common due date and non-identical sizes. Formulate a mathematical model and derive optimal properties. Develop algorithms and conduct computational experiments. Abstract: This paper considers the scheduling problem of minimizing earliness–tardiness ( E / T ) on a single batch processing machine with a common due date. The problem is extended to the environment of non-identical job sizes. First, a mathematical model is formulated, which is tested effectively under IBM ILOG CPLEX using the constraint programming solver. Then several optimal properties are given to schedule batches effectively, and by introducing the concept of ARB (Attribute Ratio of Batch), it is proven that the ARB of each batch should be made as small as possible in order to minimize the objective, designed as the heuristic information for assigning jobs into batches. Based on these properties, a heuristic algorithm MARB (Minimum Attribute Ratio of Batch) for batch forming is proposed, and a hybrid genetic algorithm is developed for the problem under study by combining GA (genetic algorithm) with MARB. Experimental results demonstrate that the proposed algorithm outperforms other algorithms in the literature, both for small and large problem instances.